Evaluating the mediator role of organizational identification in the relationship between symmetrical internal communication and individual performance of hotel employees - Eduardo Ortega; Gabriela Gomes; Neuza Ribeiro; Daniel Roque Gomes (Administrative Sciences, 2023)
The tourism industry has been distinguishing itself by promoting economic benefits and contributing to the creation of employment and opportunities in the country. This paper aims to investigate and analyze the impact of symmetric internal communication on individual performance and organizational identification, as well as to evaluate the mediating role of organizational identification in this relationship. Through the cooperation of several institutions in the tourism business sector, online surveys were applied resulting in a convenience sample of a total of 237 hotel employees in Portugal. The results of this study demonstrate that symmetrical internal communication has a positive impact on organizational identification and individual performance, and that organizational identification exerts a partial mediating effect on the relationship between symmetrical internal communication and individual performance. This study therefore extends the knowledge of the effects of important variables usually treated separately by the literature, and thus we build bridges between the communication literature and human resource management, providing information to support the structuring of new strategies.
Keywords: 350; human resources; hospitality management; tourism; hotel employee; internal communication; organizational identification